DESIGN OF SEASIDE FACILITY OF OCEAN FISHING PORT CILACAP - Maulana Razak, Rama
The full capacity problem of OFP Cilacap occured because of shallowing on cruise line and demand increasing. In order to well activate OFP Cilacap, shallowing and demand problem must be solved. The cruise line shallowing could be caused by sedimentation from Kaliyasa River or southern sea, therefore modeling of study location with MIKE21 application is required for knowing the sedimentation pattern. In order to make OFP Cilacap work as it should be, dredging for cruise line was needed corresponding to dimension and class of the ship’s design from demand forecasting. Beside of dredging, the problem of OFP Cilacap’s full capacity could be solved by designing new wharf at the northeast side of the existing port. The design of the wharf was started by demand forecasting of ship traffic, therefore the dimension of new wharf could be calculated. Furthermore, the superstructure and substructure of the new wharf were designed. The superstructure was designed to resist working loads such as dead load, live load, berthing load, mooring load, wind load, current load, wave load, and seismic load. This structure was designed as deck on pile system with concrete material, which modeled on SAP2000 application. The substructure was made of concrete spun pile which designed to consider axial bearing capacity, lateral bearing capacity, and settlements. in order to maintain the calmness of water on cruise line and harbor basins, design of breakwater is required to minimize the effect of water level rising caused by wave. To be able to design the breakwater the design wave, which inside and outside of the breakwater, was calculated by conducting a forecast in the deep sea using wind rose. Following the wave forcasting, wave rose was modeled at the port structure location by MIKE21 application. The breakwater was designed by using rubble mound type with tetrapod armor.